Pertuturan gagap dan rawatannya: kes komunikasi dalam bahasa Melayu (Jurnal Bahasa, 2004)
Stuttering is a form of human communication disorder that is accepted as a phenomenon in life. The purpose of this study is to identify the speech patterns among Malay stutterers and to compare them with those proposed by current researchers in the West. The data for this study is collected through free speech conversations between the researcher and five informants aged between 23-54 years old. The data was then analyzed for patterns in repetition, prolongation, interjection and pause. The finding indicates that patterns identified from this sample are similar to those found among stutterers in the West. As such, it is the contention of this research that remediation approach practiced in the West could also be used or adapted in designing remediation for Malay stutterers. It can also be concluded from the evidence that the major speech patterns of stutterers are universal. However, some minor differences in pattern were found between the Malay stutterers and western stutterers. These differences can be attributed to the differences in the nature of the Malay language as compared to western languages. Thus, this research recommends that the remediation approaches used in the West, although suitable for remediation of Malay stutterers, should only be used after some appropriate modification.